Eukaryotic rpL10 drives ribosomal rotation - Sulima, Sergey O. (Oxford University Press, 2014)
Ribosomes transit between two conformational states, non-rotated and rotated, through the elongation cycle. Here, we present evidence that an internal loop in the essential yeast ribosomal protein rpL10 is a central controller of this process. Mutations in this loop promote opposing effects on the natural equilibrium between these two extreme conformational states. rRNA chemical modification analyses reveals allosteric interactions involved in coordinating intersubunit rotation originating from rpL10 in the core of the large subunit (LSU) through both subunits, linking all the functional centers of the ribosome. Mutations promoting rotational disequilibria showed catalytic, biochemical and translational fidelity defects. An rpL3 mutation promoting opposing structural and biochemical effects, suppressed an rpL10 mutant, re-establishing rotational equilibrium. The rpL10 loop is also involved in Sdo1p recruitment, suggesting that rotational status is important for ensuring late-stage maturation of the LSU, supporting a model in which pre-60S subunits undergo a ‘test drive’ before final maturation.